2022
DOI: 10.2147/ijgm.s341801
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinformatic Analysis of Immune-Related Prognostic Genes in Clear Cell Renal Cell Carcinoma Based on TCGA and GEO Databases

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is a commonly occurring tumor. Through a deeper understanding of the immune regulatory mechanisms in the tumor microenvironment, immunotherapy may serve as a potential treatment for cancer patients. This study aimed at identifying the survival-related immune cells and hub genes, which could be potential targets for immunotherapy in ccRCC. Methods The gene expression profiles and clinical data of ccRCC patients were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…For example, Zhang et al (9) used bioinformatics methods to detect the gene expression profile data GSE13601 and revealed the potential mechanism of tongue squamous cell carcinoma, while Long et al (10) reported that by analyzing the gene expression profile data GSE19804, the DEGs and hub genes enhanced the cognitive of the occurrence and development of lung cancer. The GEO and TCGA databases were used by Zhang et al (11) to identify key genes and microRNAs in patients with Wilms tumor and Li et al (12) to screen immune-related prognostic genes in clear cell renal tumors. At present, there is no reliable biomarker for Wilms tumor and the molecular mechanism of its occurrence and development have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al (9) used bioinformatics methods to detect the gene expression profile data GSE13601 and revealed the potential mechanism of tongue squamous cell carcinoma, while Long et al (10) reported that by analyzing the gene expression profile data GSE19804, the DEGs and hub genes enhanced the cognitive of the occurrence and development of lung cancer. The GEO and TCGA databases were used by Zhang et al (11) to identify key genes and microRNAs in patients with Wilms tumor and Li et al (12) to screen immune-related prognostic genes in clear cell renal tumors. At present, there is no reliable biomarker for Wilms tumor and the molecular mechanism of its occurrence and development have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%